(untitled) (Journal of Global Accounting, 2025)
The nexus between corruption mitigation and corporate financial performance, particularly Return on Assets (ROA), is intricate and multidimensional. Although the curtailment of corrupt practices ostensibly enhances various facets of a firm’s fiscal robustness, ROA inclusive,this interplay is often neither linear nor unambiguous. Anchored in this complexity, the present study explores the covert yet consequential influence of ethical conduct on financial prosperity among firms listed on the Nigerian Exchange Group (NGX), with particular emphasis on the mediating role of earnings quality. Drawing from a robust dataset comprising 152 firm-year observations (originally derived from the Nigerian Stock Exchange but recontextualised herein for applicability to Nigeria), the research scrutinises the extent to which regional corruption levels—measured via corruption per capita metrics in firm-headquartered states—impinge upon the quality of reported earnings. Earnings quality is operationalised through three interrelated constructs: earnings persistence, value relevance, and predictive capacity. Employing panel regression models that control for both firm-specific and state-level heterogeneities, the study establishes a statistically significant inverse correlation between corruption and earnings quality. Elevated corruption levels are linked with compromised internal control mechanisms, exacerbated information asymmetry, and a degradation of managerial competence—all of which collectively impair the integrity of financial reporting. By situating its empirical lens within the Nigerian corporate milieu, where systemic corruption remains pervasive (Transparency International, 2023), this research augments extant literature by corroborating the salience of social capital theory. It contends that ethical behaviour functions as a latent catalyst for sustainable financial success. The findings proffer vital implications for regulatory agencies, civil society, and corporate actors in Nigeria, advocating for enhanced oversight, normative reinforcement, and institutional reforms to fortify ethical accountability. This study thus provides a critical evidentiary basis for recalibrating public policy and corporate governance frameworks in Nigeria